Access in all areas? A round up of developments in market access and health technology assessment: part 2 - Alice Beattie; Catrin Treharne; Silvy Mardiguian; Sreeram V Ramagopalan (Becaris Publishing Limited, 2023)
In this latest update, we explore the Inflation Reduction Act (IRA) enacted by the US Congress in August 2022, with the Centers for Medicare and Medicaid Services (CMS) recently releasing the list of the first ten drugs it will negotiate prices on. We also cover the consequences of price controls and rigid value assessment in Germany which have led to the withdrawal of a number of medicines. It will be important to see how the IRA balances cost-saving with holistic value assessment, incentives for innovation and patient access to treatment.